SPECIES IDENTIFICATION AND IN VITRO ANTIFUNGAL SUSCEPTIBILITY TESTING OF ASPERGILLUS ISOLATED FROM VARIOUS CLINICAL SAMPLES - HARIPRIYA BANSAL; LOVEENA OBEROI; NAVEEN PANDHI; ANURADHA MALHOTRA; TAVISHI OBEROI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Aspergillus is ubiquitous mold species present in environment in the form of spores. Infection due to Aspergillus is uncommon in immunocompetent individuals unless they possess any abnormality or have undergone any treatment with corticosteroids. In immunocompromised individuals, infection by this fungus is common among people with prolonged neutropenia, transplants, and human immunodeficiency virus infection. The symptoms are diverse, ranging from allergic reactions to invasive aspergillosis and life-threatening complications. The aim of this study is to isolate and identify Aspergillus species obtained from various clinical specimens and perform antifungal susceptibility testing (AFST). Methods: A total of 200 isolates in which positive direct microscopic findings correlated well with culture growth for Aspergillus were included. Antifungal susceptibility was performed by micro broth dilution technique according to clinical laboratory standard institute M38-A2 guidelines. Results: Aspergillus flavus was found to be predominant species followed by Aspergillus fumigatus. AFST was performed, where all Aspergillus strains exhibited low minimum inhibitory concentration (MIC) and minimum effective concentration (MEC) values for most of antifungal drugs tested except for one strain of A. flavus, which exhibited high MIC for voriconazole and high MEC for caspofungin. Conclusion: Polyenes, azoles, and echinocandin resistance are emerging in many parts of the world. Therefore, continued application of AFST combined with morphological characterization for species identification is critical in detecting the emergence of resistance among various Aspergillus species to reduce mortality, morbidity, and overcome treatment failure.